The Role of Social Media for E-Commerce in Indonesia - Nur Wahidah, Fatimatul (Economic and Business Horizon, 2024)
Social media has become an integral component of the e-commerce ecosystem in Indonesia. With features like Instagram Shopping and Facebook Marketplace, the integration between social media platforms and e-commerce creates a smoother and more effective shopping experience for consumers. This research examines the impact of social media on consumer behavior in e-commerce, focusing on the adoption of digital marketing strategies by micro, small, and medium enterprises (MSMEs). The findings suggest that social media usage can enhance customer engagement, increase brand trust, and influence purchase decisions. However, challenges related to data privacy, transaction security, and the ever-changing social media platform algorithms must be addressed by e-commerce actors. With the utilization of new technologies such as augmented reality (AR) and artificial intelligence (AI), businesses can strengthen relationships with customers, improve satisfaction, and drive Indonesia’s digital economy growth.